Experimental Study of Fiber Reinforcement Mortar and its Application in Masonry Structure - mohammad, Ishak; kumar, Niraj; jishan, Mohd (International Journal of Computer Sciences and Engineering, 2025)
Structures built with brick units bonded together by mortar in between are called brick masonry structure, and very common in India. Masonry is made up of two distinct and very different components –the brick themselves, and, the mortar which have different material properties, with brick usually having a higher strength and stiffness compared to mortar. Further mortar is usually cementations material having little tensile strength and showing brittle behavior. Use of appropriate reinforcement in mortar could substantially improve the performance of brick masonry of shear, bond, compression, energy, absorption (toughness) and crack resistance and this thesis investigated the improvements in the case when short fibers are used. An attempt was made to study the properties of fiber reinforcement mortar (FRM) and its application in masonry structures using appropriate experiments. Cement sand mortars were cast using different volumes of fibers and tested in compression and spilt tension. After narrowing down the range of suitable mix proportions, compression and shear bond tests were performed using appropriately prepared brick masonry units (BMUs) prepared with plain mortar and FRM. In the first part of study, the tests were carried out in accordance with ASTM C780, and other relevant Indian specification. For testing the BMUs, the compression tests were carried out according to standardized procedures, but an original procedure had to be developed for testing the BMU in shear. As far as the effect of fiber addition or mortar properties is concerned, it was found that as fiber is added to the matrix, the compressive strength increases by only 5-10% while the ultimate deformation decreases. However, the increase in the split tensile strength and the toughness was found to be 18-25% and 4-5 times, respectively. Whereas specimens without fiber content between 0.1% and 0.25%, showed capability to take load even after the ultimate load has been reached.